Adjusting for family size in the supplemental poverty measure. Issue 8 (4th May 2018) - Bishop, John A; Lee, Jonathan; Zeager, Lester A
ABSTRACT: We point out an anomaly in the adjustment for family size in the US Supplemental Poverty Measure (SPM). The equivalence scale for the SPM implies an instance of increasing marginal costs for an additional adult. A similar criticism of the official US poverty measure was one of several concerns that led to the creation of the SPM. We propose two possible solutions for the problem and show that eliminating the anomaly from the SPM has the greatest effect on the poverty rate for the elderly, as that group is more concentrated near the poverty line.